Does the Black middle class exist and are we members? : reflections from a research team - Khunou, Grace; Marsh, Kris; Chauke, Polite; Plank, Lesego; Igbanoi, Leo; Kgosiemang, Mabone (Emerald points., 2020)
Does the Black Middle Class Exist And Are We Membersmakes two contributions into the research of the black middle class. First, it explores how Black South Africans conceptualize middle classness. Second, it demonstrates how this conceptualization informs researchers' social identity within the Black middle class